Aflaquinolones A-G: Secondary metabolites from marine and fungicolous isolates of Aspergillus spp. - Neff, Scott A.; Lee, Sang Un; Asami, Yukihiro; Ahn, Jong Seog; Oh, Hyuncheol; Baltrusaitis, Jonas; Gloer, James B.; Wicklow, Donald T. (Journal of Natural Products, 2012)
Seven new compds. (aflaquinolones A-G; 1-7) contg. dihydroquinolin-2-one and terpenoid units have been isolated from two different fungal sources. Two of these metabolites (1 and 2) were obtained from a Hawaiian fungicolous isolate of Aspergillus sp. (section Flavipedes; MYC-2048 = NRRL 58570), while the others were obtained from a marine Aspergillus isolate (SF-5044) collected in Korea. The structures of these compds. were detd. mainly by anal. of NMR and MS data. Relative and abs. configurations were assigned on the basis of NOESY data and 1H NMR J-values, comparison of calcd. and exptl. ECD spectra, and anal. of a Mosher's ester deriv. of 2. Several known compds., including alantrypinone, aspochalasins I and J, Me 3,4,5-trimethoxy-2((2-((3-pyridinylcarbonyl)amino)benzoyl)amino)benzoate, and trans-dehydrocurvularin were also encountered in the ext. of the Hawaiian isolate. [on SciFinder(R)]
Keywords: aflaquinolone Aspergillus

Phomalevones A-C: Dimeric and pseudodimeric polyketides from a fungicolous Hawaiian isolate of Phoma sp. (Cucurbitariaceae). - Shim, Sang Hee; Baltrusaitis, Jonas; Gloer, James B.; Wicklow, Donald T. (Journal of Natural Products, 2011)
Phomalevones A-C (1-3), three new compds. with bis-dihydroxanthone and bis-benzophenone systems, were isolated from cultures of a Hawaiian isolate of Phoma sp. (MYC-1734 = NRRL 39060; Cucurbitariaceae). The structures of 1-3 were detd. by anal. of NMR and MS data. The abs. configurations of the sp3 stereocenters in the monomeric unit of 1 were assigned by application of Mosher's method, and overall abs. configurations were proposed on the basis of ECD data using both computational methods and comparisons with literature data for model compds. All three compds. showed antibacterial activity, and compds. 2 and 3 also exhibited antifungal effects. [on SciFinder(R)]
Keywords: phomalevone Phoma

Hymenopsins A and B and a macrophorin analog from a fungicolous Hymenopsis sp. - Schmidt, Lori E.; Deyrup, Stephen T.; Baltrusaitis, Jonas; Swenson, Dale C.; Wicklow, Donald T.; Gloer, James B. (Journal of Natural Products, 2010)
Hymenopsin A (1), hymenopsin B (2), and a new macrophorin analog, 2',3'-epoxy-13-hydroxy-4'-oxomacrophorin A (3), have been isolated from a fungicolous isolate of Hymenopsis sp. (MYC-1703; NRRL 37638). The structures and relative configurations of these compds. were assigned on the basis of 2D NMR and MS data, and the identity of 1 was confirmed by X-ray crystallog. anal. The abs. configuration of 2 was proposed on the basis of CD anal. using both empirical and computational methods. Compds. 2 and 3 showed antibacterial activity against Staphylococcus aureus and Bacillus subtilis. Compd. 3 was also active against Aspergillus flavus and Fusarium verticillioides. [on SciFinder(R)]
Keywords: hymenopsin Hymenopsis